Penerapan Manipulating Anyaman Pada Kain Jacquard Untuk Busana Pesta Bertema Masquerade - Badriyah, Siti; Indarti, Indarti (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
This study aims to describe the application of the weaving technique as a decorative element on a Masquerade-themed evening gown. The theme utilizes a gold and dark purple color palette dark purple conveying mystery and elegance, while gold adds luxury and warmth. The design draws inspiration from the architecture of the Palazzo Contarini Della Porta di Ferro in Venice. The research follows a six-stage creative process: problem identification, preliminary ideas, design refinement, prototype development, evaluation, and implementation. The results show that: 1) fabric manipulation through weaving is applied to women’s gowns on the bolero and the front and back of the skirt, and on men’s attire at the right front in a rectangular shape. 2) The women’s ensemble includes a dress, bolero, and small skirt; the men’s consists of a shirt, jacket, and pants. 3) The weaving is made using Jacquard fabric in two colors, with weft and warp widths of 1.5 cm each. The manipulated fabric is sewn using a machine, and the final products received good evaluations. Overall, the garments meet several design principles, effectively combining theme, technique, and aesthetics in their execution.